ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN OJEK PANGKALAN DI LOKASI PANGKALAN OJEK TASPEN KOTA MALANG - Achmad Fikri; Dwi Susilowati; Sudarti (Program Studi Ekonomi Pembangunan, 2019)
This study aims to determine whether working hours, age, work experience partially and simultaneously have a significant effect on the level of income of conventional motorcycle taxi Ojeks at Taspen Motorcycle Base The analytical tool used is Multiple Linear Regression which aims to determine whether working hours, age, work experience partially and simultaneously have a significant effect on the level of income of conventional motorcycle taxi Ojeks at Taspen Motorcycle Base. With the results of the study stating that working hours variables have a positive and significant effect on income variables. Age variables have a negative and not significant effect on income. Variable work experience has a positive and not significant effect on income.